The Influence of Leverage, Profitability, and Firm Value on Share Price: The Moderating Role of Inflation - meliza, meliza; Umar Ali Akbar, Mohammad; Putri, Anggrainy (Jurnal Ilmiah Ekonomi Islam, 2024)
The Sharia capital market in Indonesia has experienced significant growth in the number of transactions. However, the share prices of companies listed on the Jakarta Islamic Index tends to decline. Therefore, the purposes of the research were to examine the factors influencing the share prices of 30 firms listed on the Jakarta Islamic Index from 2018 to 2022. These factors include leverage, profitability, and firm value. This research also explores the role of inflation as a moderating variable on the influence of leverage, profitability, and firm value. Multiple regression analysis using random-effect model is employed to analyze the effect of leverage, profitability, and firm value on share price and the role of inflation as a moderator. The analysis results show that firm value has a significant positive effect on share price. Meanwhile, leverage and profitability do not have a significant effect. Inflation can only moderate the influence of firm value on the share price. This research contributes to determining company policies regarding improving financial performance and as a reference for the government in determining macroeconomic policies.